Assess body weight estimation, reproductive and nutrition of buffaloes at Ba kelalan - Harry Pudun, Dawat (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The buffaloes have contributed greatly in many aspects of socio-economic livelihood of rural farmers in the country. For example, they provide meat, milk, labour for the wet paddy farmers by ploughing the fields, and weeding the fields by eating out the grasses and paddy stalks after harvesting. In the process, the animals fertilize the fields through the deposit of the dung. They also provide transport to drag jungle and farm products from the fields to the store house. Besides, they act as "living bank" to the rural farmers. The animals are sold for cash whenever financial needs arise. ' The population of the animal in the country has declined steadily over the years. Some of the factors contributing towards this decline are such as the mechanization of the wet rice cultivation taking over the role of the animals providing draught power, high slaughtering rate, low reproduction, competing use of grazing lands with other uses such as agricultural activities, housing and industries. The aim of this study is to document the productive performance of buffaloes in Ba Kelalan and investigate some of the factors that influence production factors. It was concluded that the local forage quantity is inadequate, Mineral contents are low, calves mortality rate is very high and the model developed for the estimation of buffalo body weight is not significant The formula developed by Murtidjo (1998) can be used to estimate the weight of the buffalo. Female buffaloes are fertile and reproductive.